(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The clashes of interests of the great powers have led to large-scale geopolitical conflicts. Today Heartland Ukraine represents those cultural and civilizational conflicts between the major powers and a favorable geographical environment for any operations of a geopolitical and geoeconomic nature. Analysis of the course of the Russian-Ukrainian war in the Eurasia region takes us to talk about the acceleration of the civilizational confrontation, which has become Ukraine is its appropriate theater, this is the real reason for the geopolitical situation in Ukraine today, it is part of the political front of the clash of civilizations, which seeksThe United States and its European allies through it to achieve a long-awaited future goal of promoting its interests in spreading the values of liberal democracy in Eastern Europe, through the use of young democracies such as Ukraine, Georgia and Moldova, this would eventually make Russian influence in the Eurasia region weaker . On the other hand, Russia constantly aims to maintain its geopolitical and geoeconomic sphere of influence in this region and to control the military capabilities to prevent pro-Western political and economic changes. Ukraine is one of the most important post-Soviet countries for Russia. Research aims toTo answer the following questions: What is the geopolitical dimension of the RussianUkrainian war? What are the root causes of the war and the motives of the main actors in it? What are the implications of the war on international security? What will be the possible scenarios for the future if the war continues for a long time? All these questions will be answered by the research according to a geopolitical analytical vision.